Treatment of an extrahepatic portosystemic shunt by placement of a hydraulic occluder followed by a thin film band in a dog: An eventful story. Issue 3 (13th May 2022) - Bondel, Margaux; Morvan, Victor; Moissonnier, Pierre
Abstract: A 1‐year‐old, female, Yorkshire terrier was evaluated for two episodes of disorientation and severe depression. A portosystemic shunt was suspected based on clinical signs and biochemical analysis, and further confirmed by computed tomography angiography. After initial stabilisation with medical treatment, the dog underwent surgery. Invasive measurement of portal pressure after temporary complete shunt occlusion revealed a very high pressure of 40 mmHg, motivating placement of a hydraulic occluder. Several complications occurred in the postoperative period, including kinking of the device, necessitating removal of the hydraulic occluder in emergency; development of signs of portal hypertension during inflation of the hydraulic occluder, requiring partial balloon deflation; and persistent shunting, which was managed by replacing the hydraulic occluder by a thin film band.